PENGARUH JUMLAH PINJAMAN DAN KREDIT MACET SIMPAN PINJAM PEREMPUAN (SPP) TERHADAP KESEJAHTERAAN KELOMPOK SIMPAN PINJAM PEREMPUAN (SPP) UPK DAPM KECAMATAN VII KOTO DI LINGKUNGAN NAGARI LAREH NAN PANJANG SELATAN - Meidona, Syofria; Rahayu, Sari; Putra, Rahmadil (UIN MAHMUD YUNUS BATUSANGKAR, 2024)
This research was conducted to determine the effect of the number of loans and bad debts of women's savings and loans (SPP) on the welfare of the women's savings and loans group (SPP) UPK DAPM VII Koto District in the Nagari Lareh Nan Panjang Selatan Environment. The aim of this research is to partially and simultaneously examine the influence of the number of loans and bad credit for women's savings and loans (SPP) on the welfare of the women's savings and loans group (SPP) UPK DAPM VII Koto District in the Nagari Lareh Nan Panjang Selatan Environment. The population in this study was 117 and the sample in this study was 54 respondents. The data analysis technique used is multiple linear regression analysis. The research instrument test used is the validity and reliability test. The classic assumption tests used are the data normality test, multicollinearity test and heteroscedasticity test. Meanwhile, for hypothesis testing, the F test and t test are used. The analysis tool used is regression with the help of SPSS version 23 for Windows. The results of the research show that the loan amount variable has a significant effect on the welfare of the women's savings and loan group (SPP) UPK DAPM VII Koto District in the Nagari Lareh Nan Panjang neighborhood. The bad credit variable has a negative and significant effect on the welfare of the women's savings and loans group (SPP) UPK DAPM VII Koto District in the Nagari Lareh Nan Panjang neighborhood. The variables of loan amount and bad credit have a significant effect on the welfare of the women's savings and loans group (SPP) UPK DAPM VII Koto District in the Nagari Lareh Nan Panjang neighborhood. The variables of loan amount and bad credit have a joint contribution of 23.7% to the dependent variable, namely the welfare of the women's savings and loans group (SPP) UPK DAPM VII Koto District in the Nagari Lareh Nan Panjang neighborhood. while the remaining 76.3% of welfare is influenced by other variables not examined in this research.